2006
DOI: 10.1901/jaba.2006.175-04
|View full text |Cite
|
Sign up to set email alerts
|

Generalization of Tacting Actions in Children With Autism

Abstract: This intervention compared the effects of two procedures on the generalization of a tacting repertoire (labeling) in 6 children with autism spectrum disorder. In one procedure the verbal antecedent stimulus "What is she doing?" appeared together with a person performing an action; in the other procedure, the antecedent stimulus was just the presence of the action. In initial tests, children emitted tacts only when the action was presented with the verbal antecedent. Thereafter, they learned to tact an action w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 4 publications
1
24
0
Order By: Relevance
“…Also, some participants will generalize labels to novel stimuli (videos and pictures or photographs) and use language expansion targets without direct instruction. The results from this study align with past research showing that children with disabilities can learn to label actions using systematic instruction (i.e., peer, sibling, and adult modeling; Jones & Schwartz, 2004;Williams et al, 2006); however, this study expands the current literature by using a singleprompt strategy in natural contexts, assessing generalization across novel stimuli, and aligns with recommendations for direct instruction in preschool classrooms (Wolery & Hemmeter, 2011).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Also, some participants will generalize labels to novel stimuli (videos and pictures or photographs) and use language expansion targets without direct instruction. The results from this study align with past research showing that children with disabilities can learn to label actions using systematic instruction (i.e., peer, sibling, and adult modeling; Jones & Schwartz, 2004;Williams et al, 2006); however, this study expands the current literature by using a singleprompt strategy in natural contexts, assessing generalization across novel stimuli, and aligns with recommendations for direct instruction in preschool classrooms (Wolery & Hemmeter, 2011).…”
Section: Discussionsupporting
confidence: 85%
“…Examples of stimuli for instruction may include (a) live models of actions, (b) static pictures or photographs, and (c) video examples of actions. It is possible to teach multiple actions with in vivo instruction (e.g., Williams et al, 2006), but teaching certain actions may not be feasible for teachers in early childhood classrooms (e.g., person swimming). Thus, teachers may select a different medium for instruction (Welch & Pear, 1980).…”
mentioning
confidence: 99%
“…However, Williams et al (2006) demonstrated that stimulus generalization occurred after training with only one exemplar. In the current study, at least some stimulus generalization did occur following training with only one exemplar, and generalization often occurred to an equal extent as it did following MET.…”
Section: Discussionmentioning
confidence: 99%
“…Williams et al (2006) investigated the procedures of teaching tacts and assessed the conditions that would promote stimulus generalization. Participants were six children diagnosed with autism spectrum disorder.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Williams et al (2006) demonstrated that teaching children with autism to tact adult actions in the absence of cues (e.g., the teacher asking, "What is she doing?") resulted in increases in uninstructed tacts.…”
mentioning
confidence: 99%